The importance of energy efficient in wireless sensor networks - Mask, Ellon; Brown, Surgey; Lucky, Wood; Peter, Lorry (International research journal of management, IT and social sciences, 2019)
Mobile Node-based routing is an efficient routing technique compared to traditional approaches. Due to this FERP majorly data isolation is provided for sensor nodes, and the network is more energy efficient. The Mobile data collector collects data from only Family heads and forwards to the cluster head. The Node level energy saving scheme is proposed in this work. The performance of this routing protocol is assessed based on Energy consumption, Throughput, Lifetime, Packet Delivery Ratio, Energy efficiency. Most of the Energy is saved due to the introducing of mobile nodes for data collection. Apart from this, we are reducing the load for mobile data collectors also. In general, mobile data collectors have high energy resources. But it is not possible in all terrains. This FERP gives better results in military and plateaus, and irregular terrains where multihop communication is complex. This work is further enhanced by Trust node based routing to improve the lifetime of the network.